Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients - Gao, Li-chen; Wang, Di; Liu, Fang-qun; Huang, Zheng-yu; Huang, Hong-guang; Wang, Gui-hua; Chen, Xi; Shi, Qun-zhi; Hong, Li; Wu, Li-ping; Tang, Jie (European journal of clinical pharmacology, 2015)
Purpose The purpose of this study is to evaluate the association between variants in prostaglandin-endoperoxide synthase 1 ( PTGS1 ), prostaglandin F (2α) receptor ( PTGFR ), and multidrug resistance protein 4 ( MRP4 ) genes and intraocular pressure (IOP) response to latanoprost in Chinese patients with primary open-angle glaucoma (POAG). Methods The IOP response to latanoprost was evaluated by percent IOP reduction (%ΔIOP) in the treated eye with the formula %ΔIOP = (Baseline IOP values − IOP values posttreatment) / Baseline IOP values × 100 %. Polymorphisms in PTGS1 (rs3842787 and rs10306114), PTGFR (rs3753380 and rs3766355), and MRP4 (rs11568658 and rs11568668) genes were detected by direct DNA sequencing. The differences among %ΔIOP of genotypes or haplotypes were obtained by use of the Mann–Whitney U test. Association analyses were performed by multiple linear regression analysis. Results Latanoprost were prescribed to 63 subjects, 60 of which met the inclusion/exclusion criteria for the current study. Notably, the %ΔIOP in the rs11568658 GT heterozygous genotype was 10.4 %ΔIOP lower than that of GG homozygous wild-type on day 7 (15.7 ± 2.52 vs. 26.1 ± 2.88, P = 0.003), and the corresponding results in the rs10306114 AG heterozygous genotype and AT haplotype constructed by rs3753380 and rs3766355 on day 7 were 7.2 and 10.3 %ΔIOP ( P < 0.05). Interestingly, similar results were also observed on day 30 ( P = 0.008, P = 0.006, and P = 0.002, respectively). Multiple regression analysis showed that heterozygous genotypes of rs10306114, rs11568658, and carrier of AT haplotype were significantly correlated with the lower %ΔIOP. On day 30, the above variations explained 9.9, 10.7, and 17.7 % of the total variability of %ΔIOP in the Chinese POAG patients, respectively. Conclusion rs10306114, rs3753380, rs3766355, and rs11568658 single-nucleotide polymorphisms (SNPs) correlate with a response to latanoprost treatment in patients with POAG. These SNPs may be important determinants of variability in response to latanoprost.